Exaggerated auditory startle responses in multiple system atrophy: a comparative study of parkinson and cerebellar subtypes - Kofler, Markus; Müller, Jörg; Seppi, Klaus; Wenning, Gregor K (Clinical neurophysiology, 2003)
Objective: Auditory startle responses (ASRs) have recently been reported to be exaggerated in cranial and peripheral nerve supplied muscles of patients with multiple system atrophy (MSA). ASRs displayed increased probability, amplitude and duration, shorter onset latency, and reduced habituation in comparison with healthy subjects. In order to investigate whether certain ASR features may differentiate MSA subtypes, the authors studied ASRs in 21 MSA patients (olivopontocerebellar type, MSA-C: n=8, striatonigral type, MSA-P: n=13), and 17 age-matched normal controls. Methods: ASRs were elicited by binaural high-intensity auditory stimuli which differed randomly in tonal frequency and intensity (250 Hz, 90 db; 500 Hz, 105 db; 750 Hz, 105 db; 1000 Hz, 110 db normal hearing level), presented through tubal insert phones. Reflex electromyographic activity was simultaneously recorded with surface electrodes from masseter, orbicularis oculi, sternocleidomastoid, biceps brachii, abductor pollicis brevis, rectus femoris, tibialis anterior, and soleus muscles. Results: Eighteen MSA patients (86%) had exaggerated ASRs as compared to normal subjects. At group level, indices of ASR disinhibition including increased ASR probability (in extremity muscles), shortened onset latency, and enlarged response magnitude were significantly more marked in MSA-P as compared to MSA-C patients. ASR probability showed habituation in normal subjects, less in MSA-P, and none in MSA-C patients. Three MSA-patients had no ASRs except in orbicularis oculi muscle. Conclusions: Although absent ASRs may occur in some MSA patients, most of them exhibit exaggerated ASRs. This finding may reflect disinhibition of lower brainstem nuclei due to the degenerative disorder. ASRs were significantly more disinhibited in MSA-P versus MSA-C, suggesting involvement of different neural structures in the two MSA-subtypes.